Penyimpanan Minuman Serbuk Daun Sirsak Dengan Penambahan Jahe Menggunakan Kemasan Metalized Pada Variasi Suhu Dan Lama Waktu Penyimpanan - Mughofar, Dzatul Kahfi; Umiyati, Rini; Muflihati, Iffah; Affandi, Arief Rakhman (Jurnal Ilmu Pangan dan Hasil Pertanian, 2024)
Soursop leaf drink with the addition of ginger is a powder drink product which is developed into a functional food because it contains antioxidants which are good for health. Drinks in the form of powders have a low water content, so they last longer during storage. The quality of the drink can be maintained with proper packaging and storage temperature. The purpose of this study was to determine the effect of temperature and storage time of soursop leaf powder drink with the addition of ginger in metalized packaging to maintain product quality and extend shelf life. This study used a 2-factor Completely Randomized Design (CRD) with temperature treatment (10â°C and 27â°C) and storage time (1, 2, and 3 weeks), each treatment was repeated 3 times. Analysis was performed on 4 parameters, namely, water content, water activity, pH, and antioxidant activity. The results showed that there was a significant effect of temperature and storage time on water content, water activity, color, pH solubility, and antioxidant activity.Keywords: powder drink, antioxidant activity, soursop leaves, ginger